PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN PITU KABUPATEN NGAWI - Aisyahna, Amalia; Kartika, Andi (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the influence of compensation, work discipline, and work environment on the performance of elementary school teachers in Pitu District, Ngawi Regency, both partially and simultaneously, as well as to determine which variable has the most dominant effect. A quantitative approach was employed, utilizing multiple linear regression analysis with SPSS 16. The results revealed a significant simultaneous influence of compensation, work discipline, and work environment on teacher performance. Partially, compensation showed a negative and significant effect, while work discipline and work environment exhibited positive and significant effect on the performance of elementary school teachers in Pitu District, Ngawi Regency. Keywords : Compensation, Work Discipline, Work Environment, Teacher Performance